Los errores en el aprendizaje de e/le: un análisis de los heterosemánticos en las producciones escritas de los alumnos del 3° año “j” de la enseñanza media de la escuela São Francisco Xavier - VIANA, Jenifer de Lima (2019)
The present work arises with the aim of collaborating in the teaching-learning process of the Spanish language, supported in the attempt to show the importance of heterosemantics in the learning process of E / LE, thus contributing to the improvement of comprehension in Spanish language of the students. The institution chosen for this research was the São Francisco Xavier school located in the city of Abaetetuba / PA with students from the 3rd year "J". Another motivating point of the work is to understand from the analyzes of the written productions of the students of the school, that the failures of the students in the Spanish classes have a positive function in learning and that these errors are important for the learning process of the E / LE. Thus, this research was based on the investigations of Contrastive Analysis and Error Analysis. Among the theoreticians consulted are: Krashen (1981), Svartvick (1972, Corder (1971), Lado (1972) and others.